IsopiRBank: a research resource for tracking piRNA isoforms. (28th June 2018) - Zhang, Huan; Ali, Asim; Gao, Jianing; Ban, Rongjun; Jiang, Xiaohua; Zhang, Yuanwei; Shi, Qinghua
Abstract: PIWI-interacting RNAs (piRNAs) are essential for transcriptional and post-transcriptional regulation of transposons and coding genes in germline. With the development of sequencing technologies, length variations of piRNAs have been identified in several species. However, the extent to which, piRNA isoforms exist, and whether these isoforms are functionally distinct from canonical piRNAs remain uncharacterized. Through data mining from 2154 datasets of small RNA sequencing data from four species ( Homo sapiens, Mus musculus, Danio rerio and Drosophila melanogaster ), we have identified 8 749 139 piRNA isoforms from 175 454 canonical piRNAs, and classified them on the basis of variations on 5′ or 3′ end via the alignment of isoforms with canonical sequence. We thus established a database named IsopiRBank. Each isoforms has detailed annotation as follows: normalized expression data, classification, spatiotemporal expression data and genome origin. Users can also select interested isoforms for further analysis, including target prediction and Enrichment analysis. Taken together, IsopiRBank is an interactive database that aims to present the first integrated resource of piRNA isoforms, and broaden the research of piRNA biology. IsopiRBank can be accessed at http://mcg.ustc.edu.cn/bsc/isopir/index.html without any registration or log in requirement. Database URL: http://mcg.ustc.edu.cn/bsc/isopir/index.html